Chlamydia trachomatis core genome data mining for promising novel drug targets and chimeric vaccine candidates identification. (September 2021) - Aslam, Muneeba; Shehroz, Muhammad; Ali, Fawad; Zia, Asad; Pervaiz, Sadia; Shah, Mohibullah; Hussain, Zahid; Nishan, Umar; Zaman, Aqal; Afridi, Sahib Gul; Khan, Asifullah
Abstract: Chlamydia trachomatis is involved in most sexually transmitted diseases. The species has emerged as a major public health threat due to its multidrug-resistant capabilities, and new therapeutic target inferences have become indispensable to combat its pathogenesis. However, no commercial vaccine is yet available to treat the C. trachomatis infection. In this study, we used the publicly available complete genome sequences of C. trachomatis and performed comparative proteomics and reverse vaccinology analyses to explore novel drug and vaccine targets against this devastating pathogen. We identified 713 core proteins from 71 C. trachomatis complete genome sequences and prioritized them based on their cellular essentiality, virulence, and available antibiotic resistance. The analyses led to the identification of 16 pathogen-specific proteins with no resolved 3D structures, though holding significant druggable potential. The sequences of the three shortlisted candidates' membrane proteins were used for designing vaccine constructs. The antigenicity, toxicity, and solubility profile-based lead epitopes were prioritized for multi-epitope-based vaccine constructs in combination with specific linkers, PADRE sequences, and molecular adjuvants for immunogenicity enhancement. The molecular-level interactions of the prioritized vaccine construct with human immune cells HLA and TLR4/MD were validated by molecular docking and molecular dynamic simulation analyses. Furthermore, the cloning and expression potential of the lead vaccine construct was predicted in the E. coli cloning vector system. Additional testing and experimental validation of these multi-epitope constructs appear promising against C. trachomatis- mediated infection. Graphical abstract: Image 1 Highlights: Comparative proteomic analysis of 71 complete genomes of C. trachomatis was performed. 16 pathogen specific proteins having no resolved 3D structures but hold significant druggable potential were identified. The sequences of three shortlisted candidate's membrane proteins were used for designing vaccine constructs. Molecular interactions of the vaccine construct with human immune cells was validated by docking and MD simulation. The cloning and expression potential of the lead vaccine construct was predicted in E. coli cloning vector system.